Sustainable and Inherent Safe Tribological Process for Metal Nanoparticles Production - Andrea P. Reverberi (AIDIC Servizi S.r.l., 2021)
A green and sustainable process is proposed for the synthesis of metal nanoparticles (NPs) by means of a solid disaggregation in a liquid phase. A solid metal substrate, embedded in a solution containing suitable capping agents and surfactants, undergoes comminution carried out by a rotating shaft of hardness greater than the one typical of the eroded substrate. The NPs have been characterized by dynamic light scattering for particle diameter. The effect of a technical solution replacing the presence of an abrading pad and the role of different physicochemical properties of the capping agent employed to damp particle aggregation have been investigated and discussed. In three out of four experiments carried out with different capping agents, the average metal NPs diameter is smaller than 10 nm. The present process does not require a complex experimental apparatus typical of dispersion machines customarily used on an industrial scale, generally relying upon direct or indirect milling equipment. With respect to the latter techniques, the advantages offered by the process proposed here stem from a possibility of monitoring the time trend of the NPs synthesis with minimal contamination of the as-produced NPs deriving from disaggregation of the milling medium.